1995
DOI: 10.1111/j.1600-0722.1995.tb01861.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of titanium on selected oral bacterial species in vitro

Abstract: Titanium granules were tested for their antibacterial effect on strains of Streptococcus sanguis, Streptococcus mitis, Actinomyces naeslundii, Haemophilus parainfluenzae, Fusobacterium spp. and Prevotella intermedia in comparison with amalgam and two of its components, copper and tin. Glass beads were used as controls. The number of viable bacteria was estimated in samples exposed to the various materials for 1, 3, 6 and 24 h, respectively, and the viable counts were related to the baseline value. Titanium sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 22 publications
1
42
1
Order By: Relevance
“…However, the action mechanisms of several chemical agents including the metals on microorganisms have been studied, but their real inhibitory action remains still unclear (10). Moreover, metals can act as oxidant of important enzymes and proteins of the bacterial metabolism (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the action mechanisms of several chemical agents including the metals on microorganisms have been studied, but their real inhibitory action remains still unclear (10). Moreover, metals can act as oxidant of important enzymes and proteins of the bacterial metabolism (18).…”
Section: Discussionmentioning
confidence: 99%
“…: (+5511) 3091-7344, Fax: (+5511) 3091-7354. E-mail: mariojac@usp.br aluminum and vanadium, alloys of cobalt and chromium, aluminum oxide, and gold (10).…”
Section: Introductionmentioning
confidence: 99%
“…The plates were incubated under anaerobic conditions (80% N 2 , 10% CO 2 and 10% H 2 ) at 37 °C for up to 168 hours and the plates were stirred on a daily basis and the supernatant was removed, the pH was measured (pH meter -Analion PM608 Plus, São Paulo, SP) and the DMM was replaced. After 12, 24, 48 and 168 hours of incubation 19,20 , the discs were removed from the wells with sterile tweezers and the non-adherent cells were gently removed by washing with sterile saline (2 mL). After that, the discs were placed in tubes containing 1 mL of reduced transport fluid (RTF) and sonicated (Sonicador Vibra Cell -Sonics and Materials, Danbury, CT, USA) at 40 W and at a range of 5%, using six pulses of 9.9 s each.…”
Section: Biofilm Growthmentioning
confidence: 99%
“…Studies on bacterial adhesion to titanium in the oral cavity have demonstrated that the metal itself does not exhibit antibacterial activity [11], and bacteria cells adhere easily to its surface [1,18]. The adhesion of bacteria to biomaterial surface results in serious complications after surgeries and can pose a particularly huge risk for patients with long-term implants.…”
Section: Introductionmentioning
confidence: 99%